The characteristics of the educational approach in the Qur’an and the mechanisms of achieving it (An interpretive analytical study) - Ahmed nadheer yhia mzedawee ((Humanities, social and applied sciences) Misan Journal of Academic Studies, 2024)
The Holy Qur’an was and still is a source for investigators and researchers. It is a book full of precise and profound sciences and concepts that never end no matter how deeply we delve into it. The Holy Qur’an has surpassed all heavenly books with its style, organization, sciences and miracles. When reciting the Holy Qur’an and contemplating its verses, we find it repeatedly calling us to contemplation. And contemplation, and one of the reasons for this call is to find the deep and sublime meanings stored in this noble book. One of the most important matters that occupied the minds of scholars and investigators is education, its characteristics, and its methods. When we find the Holy Qur’an addressing these topics, it is better for us to go to it and ask it to provide us with these teachings. The specificity stored lies in the characteristics of the educational approach that the Holy Qur’an addresses and The methods of education that he mentions, in that this book is the word of God Almighty, protected from error and revealed to the heart of the Final Prophet (PBUH) to be a book of guidance for all humanity, and for this reason the educational teachings taken from the Holy Qur’an are the clear path and the enlightening lamp for all investigators in this field. Hence this research came under the title ((Characteristics of the educational approach in the Qur’an and the mechanisms for achieving it through an analytical and interpretive study)) to include, after clarifying its linguistic and terminological keys, an explanation of the characteristics of this approach through the study of Qur’anic verses, and among these characteristics are: The attribute of the divine source and destiny, universality, comprehensiveness, stability, immutability and change, and equality and balance that characterize this divine approach to building man and society. As for the methods to achieve this approach, they are according to extrapolation of the noble verses; The method of role models, preaching and guidance, the story, similarities and analogues of educational ideals, the exploitation of accidents, the creation of habits and values ​​in the psyche of the educated, reward and punishment, and the systematic investment of everything that is suitable for beneficial education. All of this is achieved through various methods, such as the method of leniency and gentleness, the method of enticement and intimidation, and other methods that achieve the goals of the educational curriculum in the Holy Qur’an.